POPULARITY OF LUNG ULTRASOUND IN POLAND - NATIONWIDE ONLINE SURVEY - Rafał Rajski,; Dominik Tenczyński,; Michał Kostro,; Anna Żurakowska-Zadrożna,; Wiktor Warda,; Agata Klońska,; Patrycja Trentkiewicz,; Jarosław Jarosławski, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: With the beginning of the COVID-19 pandemic, lung ultrasound has become a very popular technique, commonly used in hospitals. In recent years, we have observed a significant increase in the number of scientific publications on this technique. This paper attempts to examine the popularity of lung ultrasound in Poland among doctors of various specialties.Methods: The study included an online survey that was modular, which means it was rebuilt depending on the answers provided. Responses could be provided in the time frame of November 2022-June 2023. The questions included variables such as years of work, region of Poland, specialization, and the use of lung ultrasound in everyday practice, including in selected clinical situations.Results: The survey received 125 responses from almost all voivodeships (15/16). Among the surveyed physicians, 64% declared using lung ultrasound in their clinical practice. Lung ultrasound is most popular among physicians with up to 10 years of professional practice, while it is least popular among physicians with more than 25 years of practice. In the case of pneumonia diagnostics, most lung ultrasound users would perform an additional X-ray examination (49/80). Most of the surveyed indicated that lung ultrasound was an important examination during the COVID-19 pandemic. Moreover, it is a future-proof study that should be introduced into the medical curriculum.Conclusions: Lung ultrasound in Poland is a very popular technique, reaching up to 80% among young doctors. It is important to include this technique in diagnostic recommendations for various lung diseases and in the curriculum during medical studies. This is most likely the first publication investigating the popularity of lung ultrasound in Poland.